Autonomous biomimitic robot based multi-agent system for disaster management and rescue - Khan, Md. Raisuddin; Salami, Momoh Jimoh Emiyoka; Ahmed, Mohiuddin (2006)
This paper discusses the scope and feasibility of autonomous biomimitic robot based multi-agent systems for disaster management and rescue. Search and rescue operations in disastrous situations like earthquake, landslide, fire hazards, mineshaft breakdown etc. are still handled manually. Manual operations in these cases often fail due to complicated nature of the catastrophe. Especially in the case of human entrapment in areas inaccessible to either human or traditional rescue equipment. As such rescue operation suffers from improper strategy and even leads to unintentional further destruction due to lack of proper information along the rescue site. It is clear, proper information in and around the disaster can help successful handling of the catastrophe. Thus information like location of the survivor, state of the obstructions around him/her, state of injury, level of oxygen and hazardous gases are of crucial importance. To gather such widespread information from such difficult terrain, autonomous robots equipped with multiple sensors and capable to move inside difficult to access areas is a good choice. Autonomous biomimitic robot like Snake robot is meant to mimic motion of a natural snake, which does not possess any limb. Natural snakes can undergo wide range of motion and are able to move over rough terrains without the danger of entanglement. Slender structure of the snake body helps a snake to go inside narrow holes. Thus a snake robot able to mimic these features of a natural snake will be of extreme use in handling search and rescue operations. Snake robots equipped with multiple sensors and controlled under multiagent collaborative protocol are expected to bring about acceptable solution to disaster management and rescue. The other such biomimitic robots that can be considered in the autonomous robot team are flapping wing flyers and robot Monkeys. A team consisting of such robots will help in collecting information, distributing food and medicine in disastrous location.